Bacterial inhibition test of methanolic extracts of strawberry (Fragraia x ananassa Duchesne), lime (Citrus aurantifolia), and radish (Raphanus sativus L.), towards Streptococcus Sanguis ATCC 10556 - Anggraini, Fitri; Satari, Mieke Hemiawati; Mariam, Marry Siti (Faculty of Dentistry Universitas Padjadjaran, Indonesia, 2018)
Introduction: Caries are initiated by the plaque formation on the tooth surface, due to the interaction between food debris and bacteria in the mouth. The pioneer bacterium of plaque formation is Streptococcus sanguis. TheÂ Strawberry fruit, lime fruit, and radish root are part of the plant that contains antibacterial substances. Flavonoid, tannin, saponin, alkaloid, polyphenol, terpenoid and quinon as antibacterial substances. This study aimed to evaluate strawberry fruit, lime fruit, and radish root methanol extract can inhibit Streptococcus sanguis ATCC 10556. Therefore, strawberry, lime, and radish can be made into mouthwash, bubble gum, or toothpaste to prevent plaque formation. Methods: This study used a Kirby-Bauer diffusion test as the inhibition test. Results: The result of this study that the biggest inhibition zone was lime methanol extract 20,000 ppm, and the smallest one was radish methanol extract 5,000 ppm. Â Conclusion: Strawberry fruit, lime fruit peel, and radish root methanol extract and their combination had the effect of inhibiting bacterial growth synergistically against Streptococcus sanguis ATCC 10556.